Foreign assistance to agriculture: a win-win proposition - Pinstrup-Andersen, Per; Lundberg, Mattias K. A.; Garrett, James L. (International Food Policy Research Institute, 1995)
"This report comes out of ongoing IFPRI research on the important issue of aid to agriculture and forms part of IFPRI's broader mission of reducing hunger around the world"--Preface.